Perbandingan Hukum Keluarga Islam dan Hukum Perdata - Hanafiah, Mahmudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
Apart from being rich in culture, Indonesia is also rich in religion and belief. Each religion has certain rules as a guide to life for each of its followers. Religious diversity will of course give rise to diverse rules in social life. This is what causes the need for Indonesian Positive Law which regulates the ins and outs of the lives of all citizens. Civil Law is one of the Positive Laws in Indonesia which regulates family life. Islam, as the religion with the most adherents in Indonesia, has special rules regarding family life which are contained in the Compilation of Islamic Law (KHI). This article discusses the two models of Positive Law in the form of a comparative study with qualitative research. From the research results it can be concluded that the scope of Civil Law is wider than Islamic Family Law. Islamic Family Law originates from religious norms, while Civil Law originates from the Dutch colonial government which was enforced in Indonesia since May 1 1848. There are several things that constitute contradictions between Islamic Family Law and Civil Law, both vertically and horizontally. These contradictions need to be synchronized by paying attention to four things, namely: definition, source, scope and legal interaction.